Development of Artistic and Creative Activities for Design Students - Zhu, Lin; Lu, Jiachang (Harmonia: Journal of Arts Research and Education, 2023)
The main purpose of this scientific study is to identify key areas for the development of the artistic and creative activity of students studying the basics of design in higher educational institutions, which contributes to improving their creative abilities and developing the ability to create an innovative product design. The basis of the methodological approach in this scientific study is a combination of methods of systematic analysis of the key principles of teaching design in modern higher educational institutions with a comprehensive study of the real prospects for the introduction of innovative solutions in the process of teaching design in order to develop artistic and creative activity among future specialists in this profession. The results are the importance of developing modern students’ artistic and creative activity for design departments of higher educational institutions to improve their skills in creating artistic product design and the ability to develop innovative design were obtained. Also, the results illustrate the success of applying specific methods of training designers to implement the tasks. The practical significance of the results obtained in this research work lies in the possibility of their application in the process of teaching students of design departments of modern higher education institutions to develop their understanding of the principles of artistic design and the ability to transfer such skills to the creation of modern products with innovative design.